2022
DOI: 10.3390/molecules27051624
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Added Brewer’s Spent Grain on the Baking Value of Flour and the Quality of Wheat Bread

Abstract: This study was undertaken to determine the effect of the partial replacement of wheat flour (WF) with barley brewer’s spent grain (BBSG) and barley-buckwheat brewer’s spent grain (BBSG + B) on dough quality and bread properties, including nutritional value. The contents of brewer’s spent grain (BSG) in the blend with wheat flour were 0, 10, and 20%. The quality of the flour blends was assessed with intermediate methods and based on laboratory baking. Analyses were also carried out to determine contents of basi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 25 publications
1
10
1
Order By: Relevance
“…No significant differences in crumb porosity were observed among the bread samples compared with semolina bread, except for the bread containing 2% thin bran supplementation, in which the crumb porosity suffers deterioration, showing a non-homogeneous crumb. The results of this study disagree with [ 48 , 49 ], who observed increases in the porosity of the crumb, measured on the Dallmann scale, replacing wheat flour with brewer’s spent grain or fresh pumpkin pulp.…”
Section: Resultscontrasting
confidence: 99%
“…No significant differences in crumb porosity were observed among the bread samples compared with semolina bread, except for the bread containing 2% thin bran supplementation, in which the crumb porosity suffers deterioration, showing a non-homogeneous crumb. The results of this study disagree with [ 48 , 49 ], who observed increases in the porosity of the crumb, measured on the Dallmann scale, replacing wheat flour with brewer’s spent grain or fresh pumpkin pulp.…”
Section: Resultscontrasting
confidence: 99%
“…Protein levels on BSG ranged from 15.86% (W) to 19.77% (IPA), in accordance with Garrett et al (2021). The addition of other brewing by‐products like hot trub to BSG (Prentice & D'Appolonia, 1977; Swanston et al, 2014), and the protein content of Lager BSG being 67% higher than Ale BSG found by Robertson et al (2010) justify the higher protein levels in BSG found by Steinmacher et al (2012) and Czubaszek et al (2022). The use of soft wheat with N content under 1.9% as raw material of wheat malt production (Briggs et al, 2004) explains the significantly lower protein content of W BSG.…”
Section: Resultsmentioning
confidence: 97%
“…BSG composition is also influenced by the barley varieties, the malt type, and the malting and mashing schedules (Briggs et al, 2004). Considered a protein concentrate (Garrett et al, 2021), BSG also contains cellulose and hemicelluloses from husk, pieces of endosperm, and germ of malt grain (Czubaszek et al, 2022; Steinmacher et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Czubaszek et al [ 77 ] found that replacing wheat flour with spent grain reduced gluten yield and deteriorated its quality, leading to a decrease in the sedimentation value and stability, and increasing dough softening. These trends were attributed to the long mixing time and high shear force applied, in addition to the high fiber and protein content [ 37 , 50 ].…”
Section: Possible Uses Of Spent Grain In Food Productsmentioning
confidence: 99%
“…These trends were attributed to the long mixing time and high shear force applied, in addition to the high fiber and protein content [ 37 , 50 ]. Bread with 10% spent grain did not differ significantly from wheat flour bread in terms of appearance, crust, and crumb properties; however, the color of the bread turned from light cream to brown as the spent grain replacement increased [ 77 ].…”
Section: Possible Uses Of Spent Grain In Food Productsmentioning
confidence: 99%